Learning from GameStop: How Bandwagon Effect Influence Trading Decisions - Raden Aswin Rahadi; Subiakto Sukarno; Rivary Finan Hernawan; Ade Iusticia Putra; Ertanto Vetra; Johan Anindito Indriawan; Nasrul Syahruddin (JAF (Journal of Accounting and Finance), 2022)
This paper examines the short squeeze event of the GameStop stock in Q1 2021. While the GameStop event was not the sole example of the short squeeze phenomenon, there is a uniqueness in the event that it was orchestrated by individual investors (non-institutional) using online social media such as Reddit. Using fundamental analysis of the GME, we conclude several advantages and disadvantages, how to detect, and how to profit from short squeezes. Using the Dividend Discount Model and Free Cash Flow Model, it is also found that the GameStop stock is quite overvalued, which might be the reason for the increased number of short sells in GameStop’s stock. We also examine some of the possible causes of the occurrence of the short squeeze in a (rather likely) efficient market. Overall, this paper gives a comprehensive exposition of the phenomenon of short squeeze through this rather rare and unique GameStop event